The New Journey of China's Economic and Social Development - Xie, Fuzhan; Cai, Fang.; Li, Xuesong (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book aims at China's economic and social development, which has embarked on a new journey. It collects more than 20 major research achievements of researchers in relevant fields of the Chinese Academy of Social Sciences. These topics cover rural revitalization and anti-poverty, industrialization and manufacturing transformation, service industry upgrading, fiscal and taxation system and fiscal sustainability, major financial reform, industry and competition policy, ownership structure, new pattern of opening up, digital economy, innovation driven, financial stability, macro-control, new urbanization, regional development, ecological environment, aging population, labor market, income distribution, social governance, people's livelihood, social security, the rule of law, cultural power, and other major issues. This book helps people from all walks of life better understand and grasp the new trends, opportunities, and challenges of China's economic and social development in the future and provides useful reference for thinking about China's medium and long-term development strategy and development path.
Experiences Gained from Past 13thFive-Year Plans and Guidelines for Subsequent Plans -- Overall Evaluation and Main Experiences of the Implementation of the 13th Five-Year Plan -- Impacts of Medium and Long-term External Environmental Changes on China and Countermeasures -- Strategic Priorities of Medium and Long-term Economic and Social Development -- Research on Goals and Indicators of Mid-to-Long-Term Economic and Social Development -- Research on Rural Vitalization and Anti-poverty Strategy and Policy -- Mid-to-Long-Term Structural Adjustments of Manufacturing and Cultivation of New Competitive Advantages -- Trends and Policies for Mid-to-Long-Term Development of Service Sectors -- Mid-to-Long-Term Fiscal and Tax Reform and Financial Sustainability -- Research on Several Major Financial Reform Issues in the Medium and Long Term -- Industrial Policy and Competition Policy for Deepening the Process of Industrialization -- Mid-to-long-term Trends and Optimization Policy of the Ownership Composition -- Research on the Strategy and Policy of Constructing a New Open System at a Higher Level -- Research on Future Mid-to-Long-Term New Technologies, Digital Economy Development and Innovation-Driven Development Strategy and Major Policies -- Enhancing Resilience, Maintaining Financial Stability and Innovating macro control in China as a Major Power -- Studies on Urbanization and Regional Development Strategies and Policies -- Research on Strategies and Major Policies of Ecological Environment Protection and Climate Change Response -- Research on the Medium and Long-term Population Development and Aging -- Research on Medium-and Long-Term Employment and Labor Market Development -- Research on Middle- and Long-term Social Development Goals, Strategies and Policies -- Middle- and Long-term Social Security Development Goals, Strategic Priorities and Reform Suggestions -- Goals and Policy Research for Reform of the Public Service Financial Investment System -- Middle- and Long-term Goals and Strategies for Advancing the Rule of Law -- Medium- and long-term Goals, Strategies and Major policies for Developing a Great Socialist Culture in China.
Keywords: Economic policy; Economics; Economic sociology; Economic Policy; Political Economy and Economic Systems; Economic Sociology